Thyroid Hormone Distributor Proteins During Development in Vertebrates - Rabah, Sarah A.; Gowan, Indra L.; Pagnin, Maurice; Osman, Narin; Richardson, Samantha J. (Frontiers in Endocrinology, 2019)
Thyroid hormones (THs) are ancient hormones that not only influence the growth, development and metabolism of vertebrates but also affect the metabolism of (at least some) bacteria. Synthesised in the thyroid gland (or follicular cells in fish not having a discrete thyroid gland), THs can act on target cells by genomic or non-genomic mechanisms. Either way, THs need to get from their site of synthesis to their target cells throughout the body. Despite being amphipathic in structure, THs are lipophilic and hence do not freely diffuse in the aqueous environments of blood or cerebrospinal fluid (in contrast to hydrophilic hormones). TH Distributor Proteins (THDPs) have evolved to enable the efficient distribution of THs in the blood and cerebrospinal fluid. In humans, the THDPs are albumin, transthyretin (TTR) and thyroxine-binding globulin (TBG). These three proteins have distinct patterns of regulation in both ontogeny and phylogeny. During development, an additional THDP with higher affinity than those in the adult, is present during the stage of peak TH concentrations in blood. Although TTR is the only THDP synthesised in the CNS, all THDPs from blood are present in the CSF (for each species). However, the ratio of albumin to TTR differs in the CSF compared to the blood. Humans lacking albumin or TBG have been reported and can be asymptomatic, however a human lacking TTR has not been documented. Conversely, there are many diseases either caused by TTR or that have altered levels of TTR in the blood or CSF associated with them. The first world-wide RNAi therapy has just been approved for TTR amyloidosis.